Thin elevation: A technique for achieving thin perforator flaps - Jeong, Hyung Hwa; Hong, Joon Pio; Suh, Hyun Suk (Archives of Plastic Surgery, 2018)
Elevating thin flaps has long been a goal of reconstructive surgeons. Thin flaps have numerous advantages in reconstruction. In this study, we present a surgical method for elevating a thin flap and demonstrate the safety of the procedure. A retrospective review was performed of the electronic medical records of patients who underwent thin flap elevation for lower extremity reconstruction from April 2016 to September 2016 at the Department of Plastic Surgery of Asan Medical Center. All flaps included in this study were elevated above the superficial fascia. A total of 15 superficial circumflex iliac artery free flaps and 13 anterolateral thigh free flaps were enrolled in the study. The total complication rate was 17.56% (n=5), with total loss of the flap in one patient (3.57%) and partial necrosis of the flap in four patients (14.28%). No wound dehiscence or graft loss at the donor wound took place. Elevation above the superficial fascia is not inferior in terms of flap necrosis risk and is superior for reducing donor site morbidity. In addition to its safety, it yields good aesthetic results.
Keywords: Lower extremity; Free tissue flaps; Subcutaneous tissue